Biomarkers—A General Review. Issue 1 (17th March 2017) - Aronson, Jeffrey K.; Ferner, Robin E.
Abstract: A biomarker is a biological observation that substitutes for and ideally predicts a clinically relevant endpoint or intermediate outcome that is more difficult to observe. The use of clinical biomarkers is easier and less expensive than direct measurement of the final clinical endpoint, and biomarkers are usually measured over a shorter time span. They can be used in disease screening, diagnosis, characterization, and monitoring; as prognostic indicators; for developing individualized therapeutic interventions; for predicting and treating adverse drug reactions; for identifying cell types; and for pharmacodynamic and dose‐response studies. To understand the value of a biomarker, it is necessary to know the pathophysiological relationship between the biomarker and the relevant clinical endpoint. Good biomarkers should be measurable with little or no variability, should have a sizeable signal to noise ratio, and should change promptly and reliably in response to changes in the condition or its therapy. © 2017 by John Wiley & Sons, Inc.